72.1k views
4 votes
Simplify. (3/4√15) (16√5) A60√5 B 60√3 C 50√3

1 Answer

5 votes

Answer: OPTION B

Explanation:

You have the following expresion:


((3)/(4)√(15))(16√(5))

Mulitply them, then:


=12√(75)

Now, descompose the number inside the square root into it primes factor to simplify the expression:

75=5*5*3=5²*3

Substitute:


=12√(5^2*3)

Simplify. Then, you obtain:


=12*5√(3)


=60√(3)

User Eugene Myasyshchev
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.